Acting on Climate Finance Pledges: Inter-Agency Dynamics and Relationships with Aid in Contributor States. (April 2015) - Pickering, Jonathan; Skovgaard, Jakob; Kim, Soyeun; Roberts, J. Timmons; Rossati, David; Stadelmann, Martin; Reich, Hendrikje
Summary: Developed countries have relied heavily on aid budgets to fulfill their pledges to boost funding for addressing climate change in developing countries. However, little is known about how interaction between aid and other ministries has shaped contributors' diverse approaches to climate finance. This paper investigates intra-governmental dynamics in decision-making on climate finance in seven contributor countries (Australia, Denmark, Germany, Japan, Switzerland, the UK, and the US). While aid agencies retained considerable control over implementation, environment and finance ministries have played an influential and often contrasting role on key policy issues, including distribution between mitigation and adaptation and among geographical regions.